The Impact of Foreign Ownership on the Profitability of Commercial Banks: An Empirical Study in Vietnam - Thi Bich Duyen Pham; Thi Kieu Khanh Pham (My University, 2023)
The Impact of Foreign Ownership on the Profitability of Commercial Banks: An Empirical Study in Vietnam
Keywords: Foreign ownership